Persfektif Mahasiswa Teknologi Laboratorium Medis Terhadap Kasus Penyebaran Informasi Hoax Bidang Kesehatan Melalui Media Sosial: Perceptions of Medical Laboratory Technology Students at the National College of Health Sciences regarding Cases of Dissemination of Hoax Information in the Health Sector via SocialMedia - Dahlan Sitohang (Journal of Nursing and Health, 2025)
The study examines how Medical Laboratory Technology students at the National Health Sciences College perceive the spread of hoax information in the health sector through social media. Utilizing a quantitative approach with a survey method, the research involved random sampling from the student body at the National Health Sciences College of Surakarta. The sampling technique employed was stratified random sampling, resulting in a sample size of 100 students from the total population. Data collection was carried out via an online questionnaire distributed through Google Forms, using a closed format. Descriptive statistical analysis, including percentage analysis, mean, and median, was used to analyze the data. The findings reveal that most students in medical laboratory technology have a good understanding of hoax information and can differentiate it from legitimate news, with 75.3% of respondents being able to distinguish hoaxes from valid information. The majority of respondents are aware of hoax characteristics, such as chain messages and the absence of verification. While many students are not directly involved in spreading hoaxes, there is a growing awareness of their impact. Despite this, hoaxes continue to proliferate on social media, especially regarding health topics like Covid-19. Addressing hoaxes effectively requires a combination of institutional, technological, and informational literacy approaches to enhance public understanding and awareness of false news.